ФОРМУВАННЯ ВІДПОВІДАЛЬНОГО СТАВЛЕННЯ СТУДЕНТІВ ДО НАВЧАННЯ К Я УМОВА ЇХ МАЙБУТНЬОЇ КОМПЕТЕНТНОСТІ (Педагогіка вищої та середньої школи, 2008)
1п article the questions touching problems of formation of the crucial relation of students to the doctrine in higher educational institutions are considered.